Transient Headache and Neurological Deficits with Cerebrospinal Fluid Lymphocytosis Associated with IgM Antibodies to the Epstein-Barr Virus Viral Capsid Antigen. (17th April 2013) - Apetse, Kossivi; Breynaert, Ludovic; Butaud, Chloe; Beschet, Albert; Blanc-Lasserre, Karine; Ribouillard, Loic; Chan, Victor
Abstract : Some authors have suggested that the syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL) results from an immunological response directed against a viral agent. Here we report a case of HaNDL in an immunocompetent 19-year-old male that could support this hypothesis.